How Monocytes Contribute to Increased Risk of Atherosclerosis in Virologically-Suppressed HIV-Positive Individuals Receiving Combination Antiretroviral Therapy - Jaworowski, Anthony; Hearps, Anna C.; Angelovich, Thomas A.; Hoy, Jennifer F. (Frontiers in Immunology, 2019)
Combination antiretroviral therapy (ART) is effective at suppressing HIV viremia to undetectable levels in peripheral blood in the majority of individuals with access and ability to maintain adherence to treatment. However, ART is less effective at eliminating HIV-associated inflammation and innate immune activation. To the extent that inflammation and immune activation persist, virologically-suppressed people living with HIV (PLWH) have increased risk of inflammatory co-morbidities, and adjunctive therapies may be needed to reduce HIV-related inflammation and fully restore the health of virologically suppressed HIV+ individuals. Cardiovascular disease (CVD) is the single leading cause of death in the developed world and is becoming more important in PLWH with access to ART. Atherosclerosis is an inflammatory disease leading to acute myocardial infarction (AMI) and stroke, and epidemiological comparisons of atherosclerosis and AMI show a higher prevalence and suggest a greater risk in PLWH compared to the general population. The reasons for greater prevalence of CVD in PLWH can be broadly grouped into four categories: (a) the higher prevalence of traditional risk factors e.g. smoking and hypertension (b) dyslipidemia (also a traditional risk factor) caused by off-target effects of ART drugs (c) HIV-related inflammation and immune activation and (d) other undefined HIV-related factors. Together with improvements in ART regimens and guidelines for treatment, and a greater awareness of its impact on CVD, the HIV-related risk of AMI and stroke is decreasing but remains elevated compared to the general community. A better understanding of the mechanisms increasing atherosclerosis in PLWH are needed. Monocytes are key effector cells which are highly sensitive to inflammatory stimuli. In response to activation, they initiate formation of atherosclerotic plaques by migrating into the intima of coronary arteries and accumulating as lipid-laden foam cells. This review considers the specific role of monocytes as effector cells initiating atherosclerosis, and explores mechanisms by which HIV may promote an atherogenic phenotype and function independent of traditional risk factors. Altered monocyte function may represent a distinct HIV-related factor which increases risk of CVD in PLWH.